Risk of venous thromboembolism in hospitalised cancer patients in England—a cohort study. Issue 1 (December 2016) - Ratib, Sonia; Walker, Alex; Card, Tim; Grainge, Matthew
Abstract Background Venous thromboembolism (VTE) is a well-recognised and life-threatening complication in patients with cancer. However, the precise risk of VTE in hospitalised cancer patients in England has not been previously reported. Methods We conducted a cohort study using linked Hospital Episodes Statistics and Office for National Statistics mortality data. We determined the risk of VTE separately for 24 cancer sites following first hospitalisation for cancer (index date) and how this varied by age, proximity from hospital admission, administration of chemotherapy and calendar time. Results Between 1998 and 2012, 3, 558, 660 patients were hospitalised for cancer. The cancer sites with the highest risk of VTE during initial hospitalisation for cancer were pancreatic (4.9 %), ovarian (4 %) and liver (3.8 %). The three cancer sites with the highest risk of first VTE event within 6 months from discharge were pancreatic (3.7 %), oesophagus (3 %) and stomach (2.8 %). For most cancers, the risk of VTE within 6 months from discharge was higher amongst patients who underwent chemotherapy compared to those who did not. The impact of age on risk of VTE varied considerably between cancer sites. Conclusions The risk of VTE amongst patients hospitalised for cancer varies greatly by cancer site, age, proximity from hospital admission, and chemotherapy administration.